2009
DOI: 10.1007/s00299-008-0666-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of an Arabidopsis transcription factor WRKY25 in heat stress

Abstract: The WRKY family is one of the major groups of plant-specific transcriptional regulators. Arabidopsis thaliana WRKY25, which is induced by heat stress, is one of the group I WRKY proteins and responds to both abiotic and biotic stress. This study has examined the regulatory role of WRKY25 using wrky25 mutant and over-expressing WRKY25 transgenic A. thaliana. After 45 degrees C for different time periods, wrky25 null mutants showed a moderate increase in thermosensitivity with decreased germination, reduced hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(116 citation statements)
references
References 38 publications
2
114
0
Order By: Relevance
“…Semiquantitative RT-PCR and Northern blot analyses were performed to further confirm the T-DNA insertion mutants. Procedures for growing plants were as previously described Li et al, 2009). …”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Semiquantitative RT-PCR and Northern blot analyses were performed to further confirm the T-DNA insertion mutants. Procedures for growing plants were as previously described Li et al, 2009). …”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…WRKY proteins are a superfamily of transcription factors with potential regulatory roles related to various biotic and abiotic stress responses. Arabidopsis WRKY proteins participate in regulation of plant development (Johnson et al, 2002), material metabolism (Devaiah et al, 2007), abiotic stress (Li et al, 2009;2010;Qiu et al, 2009), seed dormancy and germination (Jiang et al, 2009). They also regulate plant responses to disease resistance and establish the corresponding pathway of signal transduction (Chen et al, 2002;Journot-Catalino et al, 2006;Yu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…4E). Hypocotyl elongation, survival rate of seedling, and electrolyte leakage assay are effective parameters in analysis of heat tolerance (Clark et al, 2004;Hong and Vierling, 2000;Li et al, 2009). The AtNRP1-overexpressing transgenic plants showed decreased thermotolerance at different growth stages and the null mutation at the AtNRP1 gene was the same as WT under heat stress, which indicated that the single-gene mutation of AtNRP1 was insufficient to alter heat tolerance.…”
Section: Discussionmentioning
confidence: 99%